Engineering of Magnetic Coupling in Nanographene - Zheng, Yuqiang; Li, Can; Zhao, Yan; Beyer, Doreen; Wang, Guanyong; Xu, Chengyang; Yue, Xinlei; Chen, Yupeng; Guan, Dan-Dan; Li, Yao-Yi; Zheng, Hao; Liu, Canhua; et al. (Physical Review Letters, 2020)
Nanographenes with sublattice imbalance host a net spin according to Lieb's theorem for bipartite lattices. Here, we report the on-surface synthesis of atomically precise nanographenes and their atomic-scale characterization on a gold substrate by using low-temperature noncontact atomic force microscopy and scanning tunneling spectroscopy. Our results clearly confirm individual nanographenes host a single spin of S=1/2 via the Kondo effect. In covalently linked nanographene dimers, two spins are antiferromagnetically coupled with each other as revealed by inelastic spin-flip excitation spectroscopy. The magnetic exchange interaction in dimers can be well engineered by tuning the local spin density distribution near the connection region, consistent with mean-field Hubbard model calculations. Our work clearly reveals the emergence of magnetism in nanographenes and provides an efficient way to further explore the carbon-based magnetism.
CRIS-Team Scopus Importer:2023-03-20